Assessment of performance metrics for fusion network - Gupta, Rohan; Singh, Gurpreet; Kaur, Amanpreet (Kuwait Journal of Science, 2021)
The arrangement which does not necessitate any infrastructure for doing discussion among nodes is called as mobile ad-hoc network. In this paper the direction-finding technique which is mixture of particle swarm optimization and ant colony optimization technique has been designed. To compute the usefulness of the intended technique the outcome of intended technique is evaluated with respect to several assessment metrics specifically routing overhead, packet delivery ratio and throughput. The designed technique is judged against several alternatives of particle swarm optimization technique and ant colony optimization technique i.e. EDNR+PSO, AntChain Protocol, Improvised Ant Colony Routing (IACR) and ANTALG. Open source simulator NS 2.3 is employed for carrying out the simulation. From the outcome it has been verified that the designed technique is finest in contrast to other alternatives of particle swarm optimization and ant colony optimization Routing overheads of the designed algorithm are reduced in contrast to other methods.